Miejsce pochodzenia dziecka w kanonicznym porządku prawnym - Dzierżon, Ginter (Prawo Kanoniczne, 2010)
In the presented article, the author not only presented the interpretation of canon 101 §§ 1-2 CIC but also di scussed the issue of child’s place of origin in a wider context showing also the legal arguments of this norm. According to the presented research, in the canonical system, the category child’s place of origin has a legal character. It is based on legal fiction since it is one’s place of birth that determines one’s origin but the place of living of one’s parents (or parent) on the place where a child was found. The author believes that in the current legal order, the rules codified in canon 101 §§ 1-2 CIC are becoming less and less significant because nowadays the instruction included in this regulation has no clear reference to order areas of the Code. This results from the fact that in the new version of the Code, there are no rules included in 1917’s canon 544 § 2, 956 CIC which were rescinded. On the basis of the documentation of the revision of the 1917’s Code, the author also demonstrated that it was eventually decided that the abovementioned regulations should be maintained because of the possibility of their application in inter extra Code or particular law.